MASA DEPAN TOLERANSI: “A Common Word” Di Kalangan Pelajar Sekolah Menengah Di Kota Pekalongan - Akhwanudin, Afith (STAI Syubbanul Wathon Magelang, 2024)
The tolerant character of future generations is important in an increasingly heterogeneous society. They must have a vision that is able to work together beyond ethnic and religious differences. This research discusses the understanding and commitment of senior high school students in the city of Pekalongan regarding the universal human values ​​taught in each religion which are the basis for tolerance between humans as creatures. This research tried to find senior high school students’ understanding of the values ​​of